A organização dos processos administrativos no âmbito de uma instituição federal de ensino superior - IFES - Rosa, Cleber Domingos Trindade (2013)
This dissertation is to identify and standardize the training process under a Federal Institution of Higher Education, aimed at qualifying the services rendered by Protocolizadora Unit. The UFSM, as well as other public institutions of higher education, is constantly expanding and institutional development, making it imperative for their managers ' commitment to seek the best methods for the implementation of its activities. Thus, were revised operational practices in order to promote changes in organizational management systems. The research is a case study characterized as descriptive qualitative approach. To achieve the research objective, we carried out a study on legislation, standards and references on the subject, by document analysis, unstructured interviews, and direct observation of the researcher. Through standardization of procedures and routines related to the assessment process, we sought to reduce the possibility of error, streamline public administration, and to ensure citizens the right to obtain information of private or collective interest. 68 (sixty-eight) subjects , which amounted to one hundred (100) administrative processes encompassing more than 93 % of those fined percentage, according to a survey of the period between the years 2000 to 2012 were analyzed. Based on the data collected was elaborated for the university community and other institutions a manual to standardize administrative processes.